The effects of celebrity gossip on trust are moderated by prosociality of the gossipers. (1st June 2019) - Rudnicki, Konrad; De Backer, Charlotte J.S.; Declerck, Carolyn
Abstract: Previous research suggests that gossip serves several functions in regulating group dynamics (e.g. bonding, entertainment) and is preferentially used by prosocial individuals to protect the group from exploitation. However, it is still unclear what mechanisms underlie these functions and compel prosocial people to gossip. Because gossip provides information about the attitudes and moral views of an interaction partner we hypothesized that for prosocial individuals it functions as a cue that enables trust to be established, even among strangers. We conducted an experiment with 122 female participants who did not know each other prior to the study. They were asked to gossip about celebrities (the most likely form of gossip between strangers) or perform a creativity task for 20 min in pairs before playing a trust game. Participants were categorized as prosocial or proself based on their social value orientation (SVO). To additionally test if the effect of gossip on trust differs in real-life interactions and online, participants interacted either face-to-face or online. The results show that, irrespective of the environment, prosocial women trusted their interaction partners more after gossiping, whereas proself women trusted their partners less.